2017
DOI: 10.1111/myc.12707
|View full text |Cite
|
Sign up to set email alerts
|

Sensitisation to fungi in atopic dermatitis patients over 14 years of age and the relation to the occurrence of food hypersensitivity reactions

Abstract: The aim of this study was to evaluate if there is some relation between the sensitisation to fungi and the occurrence of food hypersensitivity reactions in atopic dermatitis patients aged 14 years and older. Complete dermatological and allergological examination was performed in all included patients; the occurrence of food hypersensitivity reactions was recorded and the sensitisation to mixture of fungi was examined (skin prick test, specific IgE). The statistical evaluation of the relation between the sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 73 publications
(179 reference statements)
3
5
0
Order By: Relevance
“…In our previous studies we confirmed, that sensitisation to fungi (according to the examination with extract sIgE and skin prick test) was recorded in 30% patients suffering from atopic dermatitis Čelakovská, Bukač, Ettler, Vaneckova, Krcmova, et al, 2018).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In our previous studies we confirmed, that sensitisation to fungi (according to the examination with extract sIgE and skin prick test) was recorded in 30% patients suffering from atopic dermatitis Čelakovská, Bukač, Ettler, Vaneckova, Krcmova, et al, 2018).…”
Section: Discussionsupporting
confidence: 65%
“…In our previous publications, we demonstrated our results regarding the sensitisation to fungi in atopic dermatitis patients with the examination of skin prick test and specific IgE (Čelakovská, Bukač, Ettler, Vaneckova, Krcmova, et al, 2018;.…”
Section: Introductionmentioning
confidence: 69%
“…[43] In our previous study we confirmed that patients suffering from sensitization to fungi suffered significantly more from food hypersensitivity reactions to nuts and fishes. [44] The antifungal effect of plant proteins (defensins and lipid transfer proteins) probably cannot be applied, as also the antifungal effect of fatty acids methyl esters in fish. [44] In India, Bains and Dogra determined the prevalence of positive SPT in patients with chronic allergic skin disorders.…”
Section: Discussionmentioning
confidence: 99%
“…[44] The antifungal effect of plant proteins (defensins and lipid transfer proteins) probably cannot be applied, as also the antifungal effect of fatty acids methyl esters in fish. [44] In India, Bains and Dogra determined the prevalence of positive SPT in patients with chronic allergic skin disorders. [45] Fifty patients with chronic allergic disorders were recruited in this study.…”
Section: Discussionmentioning
confidence: 99%
“…We found no relation between the sensitisation to fungi and the occurrence of food hypersensitivity reactions to other foods (tomatoes, kiwi, apples, spices, oranges, capsicum, celery, carrots and strawberries). 16 Among the over 100 000 fungal species reported, only a few hundred have been described as opportunistic pathogens causing human illness through 3 specific mechanisms: direct infection of the host, elicitation of deregulated immune responses and toxic effects due to secondary metabolites. 17-20…”
mentioning
confidence: 99%